Nursing students' awareness of global climate change: A descriptive and cross-sectional study - Kilic, Hulya Firat; Cevheroglu, Seda; Gok, Nur Demet (Wiley, 2024)
Objective: This study aimed to determine nursing students' awareness of global climate change. Design: This descriptive and cross-sectional study was conducted with 302 undergraduate nursing students from a foundation university in Northern Cyprus during the spring semester of the 2021-2022 academic year. A descriptive information form and the Awareness Scale of University Students about Global Climate Change (ASUSGCC) were used for data collection. Results: The mean ASUSGCC score was 3.54 +/- 0.64, and the participants received the lowest and highest scores from the awareness of the causes of global climate change (3.54 +/- 0.64) and awareness of the effects of global climate change on the natural and human environment (4.03 +/- 0.70) subscales, respectively. A statistically significant difference was observed between the Global Climate Change scores and the year of education, with fourth-year students obtaining significantly higher scores (p < .05). Conclusions: The study found that nursing students have a moderate level of awareness of global climate change. To raise the level of awareness among these undergraduates, who will be future healthcare professionals, we recommend including climate change awareness in the national nursing curricula.
Keywords: awareness; climate change; global climate; nursing students